Public organizational performance: Policy implementation in environmental management in Bandung City - Engkus Engkus; Ahmad Syamsir (Masyarakat, Kebudayaan dan Politik, 2021)
This study is motivated by the performance of the Department of Environment and Hygiene Services of Bandung City which has not been optimal. This is partly due to the poor services in the underground water mining sector, thus it is a current synthesis. This study aims to explore and discuss organizational performance through policies that have been implemented. The research method used was a descriptive qualitative approach, using data collection techniques of observation, interviews, and literature study. The results of the study indicate that the performance of public organizations has not been optimal due to low responsibility, responsiveness, and accountability, as well as internal constraints that occur structurally, the competence of human resources and non-human resources that are not appropriate so that it affects performance in the underground water mining sector that does not comply rule. This study concludes that the organizational structure and human resources in public organizations have not been effective and efficient so that the completion of public services is hampered.